The incidence and risk factors for shipping fever in horses transported by air to Hong Kong: Results from a 2-year prospective study. (August 2016) - Hurley, M.J.; Riggs, C.M.; Cogger, N.; Rosanowski, S.M.
Highlights: Data were collected from 81 shipments of horses transported to Hong Kong by air. The incidence risk of shipping fever was 10.8 per 100 horses. The proportion of shipments that contained horses with shipping fever was 60%. Risk factors identified were country of origin and month of arrival. Recognition of at-risk shipments helps focus attention on preventative strategies. Abstract: A 2 year prospective study was performed between February 2011 and January 2013 to determine the incidence and risk factors for shipping fever (SF) in horses transported by air to Hong Kong (HK). Using a questionnaire, data were collected from professional flying grooms regarding the journey to HK and horses in the shipment. Horses were monitored in quarantine for 2 weeks after arrival in HK, and clinical signs of SF recorded. Poisson and logistic regression models were used to identify risk factors for SF at the horse and shipment levels. The study analysed data from 869 horses on 81 flights arriving from Australia ( n  = 24), New Zealand (NZ; n  = 18), the United Kingdom (UK; n  = 33) and the United States of America (USA; n  = 6). The incidence risk of SF was 10.8 per 100 horses and the proportion of shipments with at least one horse that developed SF was 49/81 (60%). The study identified that the rate per shipment of SF in shipments of horses originating from NZ, the USA and the UK was 2.40 (95% confidence interval [CI] 1.22–4.71), 2.43 (95% CI 0.66–8.89) and 3.08 (95% CI 1.60–5.93) times the rate of SF compared to Australia. Shipments arriving in HK during March and May were 5.61 (95% CI 1.55–20.31) and 4.51 (95% CI 1.43–14.26) times more likely to contain horses that developed SF compared to shipments arriving in January. The identification of these risk factors and the recognition of at-risk shipments will help focus attention on preventative strategies.